THE RISK OF PLACENTA ACCRETA FOLLOWING PRIMARY ELECTIVE CAESAREAN DELIVERY - QURESHI , AI; ANWAR, Z; RAZZAQ , M; TAJ , N (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in Gynecology Department, Nishtar Medical Hospital, to assess the risk of placenta accrete after the primary (first) emergency or elective c-section. The study was conducted on data from women with placenta accreta who underwent primary C-sections from 2017 to 2020. Analysis was done through variably matched sets. Data on cases and controls was extracted from hospital records. There were 70 women in the study group and 115 in the control group. Results showed that of 70 cases, 40 (57.1%) had placenta accreta, 16(22.8%) had placenta increta, and 14 (20%) had placenta percreta. A significantly higher number of cases than controls had primary elective c section (P<.001). The elective C-section had a significantly higher risk of subsequent placenta accreta than the emergency C-section (P=0.025). Thus, it was concluded that the primary elective C-section modifies the risk of subsequent placenta accreta.